Interactions of Some Organic Compounds with α-, β- and γ-Cyclodextrins: A Molecular Mechanics Study - I. El-Barghouthi, Musa; S. Al-Degs, Yahya (Asian Journal of Chemistry, 2010)
In the present work, molecular mechanics calculations using amber force field were conducted to study the complexation of some organic compounds varied in structure and functional groups with α-, β- and γ-cyclodextrins to evaluate host-guest binding energies. Results indicate that guest-host interactions have a significant role as a driving force in complex formation but not the dominant one. Also mode of solute interaction with cyclodextrin in the optimal complex geometry are not the same for different types of cyclodextrins. Results also indicate that relaxation of the macrocycle structure of the host is important as a driving force for complexation with α- and β-cyclodextrins, where for γ-cyclodextrin, this factor is low.